Strategy the logic of war and peace - Luttwak, Edward (Cambridge Belknap Press of Harvard University Press, 2001)
If you want peace, prepare for war.? ?A buildup of offensive weapons can be purely defensive.? ?The worst road may be the best route to battle.? Strategy is made of such seemingly self-contradictory propositions, Edward Luttwak shows―they exemplify the paradoxical logic that pervades the entire realm of conflict.
Includes bibliographical references (p. 299-303) and index.
Keywords: Strategy